2017
DOI: 10.1590/0102-6720201700020005
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Expresion of the Genes Mutyh and Ogg1 in Patients With Sporadic Colorectal Cancer

Abstract: Background: MTUYH and OGG1 genes have importance in the base excision repair systems of oxidized DNA bases. Modification of the tissue expression of these genes is related to the increased risk of developing colorectal cancer. Aim: To evaluate the tissue expression of MUTYH and OGG1 comparing normal and neoplastic tissues of patients with sporadic colorectal cancer and to correlate it with clinical and histopathological variables. Method: MUTYH and OGG1 tissue expression was quantified by RT-PCR in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In sporadic CRC, unrepaired 8-oxo-dG adducts induce mutations in proto-oncogenes, such as KRAS and tumor suppressor genes and, also, both MUTYH and hOGG1 were found to be downregulated in neoplastic human colon tissues compared to adjacent tissues [78]. The concerted action of MUTYH and hOGG1 is illustrated in Figure 1.…”
Section: Sporadic Colorectal Cancermentioning
confidence: 97%
“…In sporadic CRC, unrepaired 8-oxo-dG adducts induce mutations in proto-oncogenes, such as KRAS and tumor suppressor genes and, also, both MUTYH and hOGG1 were found to be downregulated in neoplastic human colon tissues compared to adjacent tissues [78]. The concerted action of MUTYH and hOGG1 is illustrated in Figure 1.…”
Section: Sporadic Colorectal Cancermentioning
confidence: 97%
“…Recent research also suggests that patients with colorectal cancer have lower MUTYH expression in cancer tissues compared with normal tissues (19). Meanwhile, the MUTYH gene was found to present reduced expression in more advanced stages of colorectal cancer, and lower MUTYH expression may contribute to worse patient prognosis (12). In the present study, the association of MUTYH with CDDP resistance in ESCC cells was analyzed.…”
Section: Downregulation Of Mutyh Contributes To Cisplatin-resistance Of Esophageal Squamous Cell Carcinoma Cells By Promoting Twist-mediamentioning
confidence: 76%
“…MUTYH is a key component of the system of base excision repair (BER), which is able to remove the oxidized bases paired erroneously, thereby ensuring the maintenance of DNA integrity (10,11). It has been confirmed by experimental evidence that MUTYH has an important role in various cancer types; it was reported that modification of the tissue expression of MUTYH is associated with the elevated risk of development of various cancer types, such as colorectal cancer, lung cancer, esophageal carcinoma, thyroid cancer and head and neck cancer (12)(13)(14)(15)(16)(17). Mutations in MUTYH reduce BER effectiveness and predisposition to cancer (17,18).…”
Section: Downregulation Of Mutyh Contributes To Cisplatin-resistance Of Esophageal Squamous Cell Carcinoma Cells By Promoting Twist-mediamentioning
confidence: 94%
“…The main mechanism involved in the removal and repair of oxidized DNA bases with the involvement of lesion-specific DNA glycosylases is base excision repair (BER) [ 10 , 11 , 12 ]. Additionally, both MUTYH and hOGG1 were found to be downregulated in malignant human colon tissues in comparison with adjacent tissues [ 13 ]. The role of BER glycosylases in the transition from early adenoma to CRC has clearly been documented on hereditary syndromes MUTYH -associated polyposis (MAP) and NTHL1 -associated tumor syndrome (NATS) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%